FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PADA PERUSAHAAN PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (Students' Journal of Accounting and Banking, 2015)
The purpose of this study was to analyze the factors that affect the price of shares in a mining company listed on the Indonesia Stock Exchange. Factors that affect the stock price consists dar Earning Pershare, Return on Investment, Price Book Value, Profit Margin, Debt Equity Ratio, Devident Pershare. The population in this study is a mining company in the period 2009-2013. The sample in this study were selected using purposive sampling method. The analysis tool used is multiple linear regression. The results showed that Pershare Earnings , Return On Investment and Price Book Value influence on stock prices while the variable profit margin , Debt Equity Ratio , Devident Pershare no effect on stock prices at a mining company listed on the Indonesia Stock Exchange.Keywords: Earning Pershare, Return On Investmen, Price Book Value, Profit Margin, Debt Equity Ratio, Devident Pershare, Stock Price